2021
DOI: 10.1108/mbe-07-2020-0100
|View full text |Cite
|
Sign up to set email alerts
|

ISO 9001: a vaccine for time of crisis

Abstract: Purpose ISO 9001 is applied by hundreds of thousands of companies throughout the world. For this reason, its effect on company results has been extensively studied. However, the results of those studies are inconclusive and sometimes contradictory. More in-depth research, with a new approach, is therefore necessary. The purpose of this paper is to analyse whether ISO 9001-certified companies suffered the effects of the financial and economic crisis of 2007–2008 to a lesser degree than non-certified ones. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…They found that perception of an ISO 9001 certified entity depends on the awareness level of the customer organisation and its people about this standard. Zayas-Mateo and Martínez-Lorente (2021) although did not establish direct influence of ISO 9001 on consumers but reported that it results in improved income and profits which is possible when consumers view it favourably. Lew and Sulaiman (2014), without studying any specific standard, observed that perception of good product quality increases purchase intention of consumers.…”
Section: Methodsmentioning
confidence: 94%
“…They found that perception of an ISO 9001 certified entity depends on the awareness level of the customer organisation and its people about this standard. Zayas-Mateo and Martínez-Lorente (2021) although did not establish direct influence of ISO 9001 on consumers but reported that it results in improved income and profits which is possible when consumers view it favourably. Lew and Sulaiman (2014), without studying any specific standard, observed that perception of good product quality increases purchase intention of consumers.…”
Section: Methodsmentioning
confidence: 94%
“…This requirement continued in the 2008 revision as well as in the current version, i.e. ISO 9001:2015 (Domingues et al ., 2019; Zayas-Mateo and Martínez-Lorente, 2021). Since IATF 16949:2016 uses the requirements of ISO 9001:2015 as its base requirements, the continual improvement requirements of ISO 9001:2015 automatically become essential requirements of IATF 16949:2016.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is noteworthy that ISO 9001 does not mandatorily require firms to monitor operational efficiency and shareholder value. Apart from the longitudinal study, other research that explored performance improvement in organisations due to quality management systems predominantly used feedback and perception ratings rather than real numbers from organisations (Arumugam et al ., 2008; Chen and Chang, 2017; Chiarini et al ., 2020; Eve and Sprimont, 2016; Psomas, 2013; Yadav et al ., 2020; Zayas-Mateo and Martínez-Lorente, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have classified reputational signals as either formal or informal. In this study, we focus on formal reputational signals that are validated externally, such as third-party accreditation and certification (De Camargo Fiorini et al , 2019; Zayas-Mateo and Martínez-Lorente, 2021) that depict a comparatively stronger form of a nonprofit accountability signal (Becker, 2018; Gugerty, 2009). Third-party certification is a formal, independent recognition by an external organization that confirms that a prescribed standard of performance has been achieved (Martí-Ballester and Simon, 2017).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…A number of studies have documented that organizations use different types of reputational signals such as third-party certification and accreditation, reporting of organizational documents, and other voluntary accountability measures to restore organizational reputation and trust (Becker, 2018; Bekkers, 2010; De Camargo Fiorini et al , 2019; Gugerty, 2009; Zayas-Mateo and Martínez-Lorente, 2021). In the business sector, for example, environmental, quality and other management systems and their corresponding standards have proliferated globally, and many organizations have gained International Organization for Standardization (ISO) 9000, 9001 or 14,001 certification (Caro and García, 2009; Chiarini, 2017; Martí-Ballester and Simon, 2017).…”
Section: Introductionmentioning
confidence: 99%